Geochemical Negative Emissions Technologies: Part II. Roadmap - Maesano, Cara N.; Campbell, James S.; Foteinis, Spyros; Furey, Veronica; Hawrot, Olivia; Pike, Daniel; Aeschlimann, Silvan; Reginato, Paul L.; Goodwin, Daniel R.; Looger, Loren L.; Boyden, Edward S.; Renforth, Phil (Frontiers in Climate, 2022)
Geochemical negative emissions technologies (NETs) comprise a set of approaches to climate change mitigation that make use of alkaline minerals to remove and permanently store carbon dioxide (CO2) as solid carbonates or dissolved ocean bicarbonate. This perspective piece accompanies the comprehensive review of geochemical NETs (Campbell et al., 2022) presented by the same authors, and complements it by offering our perspective on future directions for the development and deployment of geochemical NETs at gigaton scale. We present our perspective in the form of a roadmap, which assesses needs and high-priority initiatives across six key elements required for the responsible and effective deployment of climate solutions: i) technical readiness, ii) social license, iii) demand, iv) supply chains, v) human capital, and vi) infrastructure. We put forward proposals for: specific initiatives to be undertaken; their approximate costs, timelines, and sequencing; and roles that different types of actors could play in undertaking them. Our intent is to further progress towards a working consensus among researchers and practitioners about initiatives that merit resourcing and action, primarily focusing in the near-term.